2004
DOI: 10.1111/j.1365-263x.2004.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct pulp capping with mineral trioxide aggregate in a primary molar: a case report

Abstract: A case is presented in which pulp capping was performed on a right first mandibular primary molar in a 7-year-old male patient. An alkaline cement powder based on mineral trioxide aggregate (MTA) was used for pulp capping. There were no pathological findings either on a radiograph taken after one year or on clinical examination after 18 months, and the right first mandibular primary molar remained vital after capping with MTA. Further clinical investigation of MTA for direct pulp capping of primary teeth shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Results represent the mean AE SD of triplicates. Based on a Student t test, the differences between the control and MTA group (*) are significant at p # 0.05. capping agent (29)(30)(31) with the formation of a dentinal bridge. Previous reports have shown the effects of MTA on pulp cells (32,33) and also compared these effects with those with calcium hydroxide (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Results represent the mean AE SD of triplicates. Based on a Student t test, the differences between the control and MTA group (*) are significant at p # 0.05. capping agent (29)(30)(31) with the formation of a dentinal bridge. Previous reports have shown the effects of MTA on pulp cells (32,33) and also compared these effects with those with calcium hydroxide (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Primary Teeth Pulp Capping. The results from a case report and a case series study indicated that MTA can be successfully used for direct pulp capping of primary molars (65,66). In a prospective clinical investigation of pulpcapped primary molar teeth either with CH or MTA, Tuna and Olmez (67) reported clinical and radiographic success after 24 months for both materials.…”
Section: Vital Pulp Therapymentioning
confidence: 93%
“…After its approval in 1998 by the US Food and Drug Administration, the use of MTA has expanded to other applications such as direct pulp capping (Aeinehchi et al. 2003, Bodem et al. 2004, Iwamoto et al.…”
Section: Introductionmentioning
confidence: 99%
“…2006). However, only a single case study with a long‐term clinical and radiographic follow‐up involving primary teeth has been reported (Bodem et al. 2004).…”
Section: Introductionmentioning
confidence: 99%